대두 분말의 단백질 농축을 위한 마찰하전 정전선별 연구 - 백상호(Sang-Ho Baek); 김성민(Seong-Min Kim); Tsogchuluun Davaadorj; 전호석(Ho-Seok Jeon) (Han'guk Sikp'um Yŏngyang Kwahakhoe chi, 2022)
본 연구에서는 대두 분말을 대상으로 마찰하전 정전선별을 적용하여 단백질 농축 가능성을 평가하였다. 모든 실험에서 금속 하전재질은 플라스틱 하전재질보다 상대적으로 단백질 함량이 높고 회수율은 낮은 경향을 보였다. 하전장치의 길이, 전극의 전압 세기는 주목할 만한 변화와 경향을 보이지 않아 선별효율에 영향을 미치는 인자들이 아니었다. 반면, 질소 가스의 양 및 하전장치 내경은 pipe line 내의 가스 속도와 관련이 있으며, 빨라질수록 단백질 함량은 증가하고 회수율은 감소하는 경향을 확인하였다. 대두에 존재하는 지방의 제거는 선별효율에 긍정적인 영향을 미쳤다. 전지방 대두 분말의 단백질 증가율은 1~4%지만, 지방이 약 30% 제거된 대두 분말의 단백질 증가율은 4~6% 수준이었으며, 회수율은 전체적으로 향상되었다. 대두 분말은 일정량의 수분과 비장을 포함하는 미립자로 응집이 쉽게 발생할 수 있는 조건을 갖추고 있다. 따라서 입자의 응집에 영향을 주는 지방과 수분 제거의 전처리와 입자의 분산은 마찰하전 정전선별을 통한 대두의 단백질 농축에 중요한 조건으로 판단된다. Wet fractionation techniques, which are conventional plant protein production methods, reduce the quality and functionality of protein ingredients. Tribo-electrostatic separation, which is a dry fractionation technique, can be a suitable alternative. In this study, the protein concentration potential of soybean powder through tribo-electrostatic separation was evaluated. Metal charging material showed a tendency to have a higher protein content and lower recovery than plastic. The charger length and applied voltage of the electrodes did not show any noticeable changes and trends. Nitrogen (N2) gas and charger internal diameter were related to the gas velocity in the pipeline, and as the gas velocity increased, the protein content increased and the recovery decreased. The removal of fat had a positive effect on separation efficiency. The increase in the protein concentration from full-fat soybean powder was 1∼4%, whereas that of de-fatted (about 30%) soybean power was 4∼6%. In conclusion, the removal of fat, which affects particle aggregation and particle dispersion, is considered an important condition for protein concentration through tribo-electrostatic separation. KCI Citation Count: 0